Uso do D-Limoneno como retardante de envelhecimento de emulsão asfáltica aplicada em tratamento superficial por penetração - Silva, Ataslina de Paula da (2023)
Chip Seals (CS) are flexible coatings that use thin layers of asphalt binder obtained by breaking the emulsions, making them more susceptible to the harmful effects of aging and causing them to disintegrate. This study investigated whether the D-Limonene (D-L) acts as a slowing agent for the oxidative aging of CS binders. A four-phase experimental program was developed. The first two dealt with the collection and characterization of the materials, in addition to preparing the modified emulsion at the blends of 0.5%, 1.5%, 2.0%, and 3.0% D-L. The third phase gathered physical, chemical, and rheological tests to assess the unaged and long-term aged condition. The fourth phase involved an evaluation of performance specifications for CS, also including an economic analysis. The results of the empirical characterisation indicated the acceptability of the modified emulsion in terms of the current technical parameters. It was observed by the chemical analysis that the D-L decreased parameters related to aging, such as the functional groups detected in the infrared and in the proportion of asphaltenes, as well as in their conglomerates. The 1.5% D-L content was selected because it was the percentage with the greatest chemical changes regarding aging. This content was evaluated in further analyses regarding to the binder emulsification process and the events of thermal degradation. There was a decrease in stiffness and an improvement in the elastic response to different temperatures in the rheological behavior. The adhesiveness strenght increased after the long-term aging of the materials, and the D-L intensified this effect and reduced the susceptibility of the samples to the harmful effects of water. Also, the adhesiveness showed a good correlation (R2) with the empirical parameter of Saybolt-Furol viscosity. Regarding the loss of aggregates, the modification increased the CS traffic volume, indicating an improvement in performance for different periods of environmental exposure. Finally, using D-L as an additive represented a 15% increase in execution costs. Thus, it was concluded that the behavior of the emulsion modified by D-L was favorable in terms of properties related to performance and under the conditions investigated; however, the application of this material in paving would be unattractive from an economic point of view. These findings indicated that, based on a market dynamic more favourable economically, the D-L has an application considered as promising like an additive that delays the aging of emulsions for TSP.